2011
DOI: 10.1186/1759-8753-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Alu pair exclusions in the human genome

Abstract: BackgroundThe human genome contains approximately one million Alu elements which comprise more than 10% of human DNA by mass. Alu elements possess direction, and are distributed almost equally in positive and negative strand orientations throughout the genome. Previously, it has been shown that closely spaced Alu pairs in opposing orientation (inverted pairs) are found less frequently than Alu pairs having the same orientation (direct pairs). However, this imbalance has only been investigated for Alu pairs sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…It has been shown that inverted Alus, even at 86% identity, efficiently stimulate recombination when separated by b20 nt, while recombination still occurs at 80% identity (Lobachev et al, 2000;Stenger et al, 2001). In a recent work evidence is presented about deletions of Alu repeat pairs in inverse orientation separated by long distances, up to 350,000 nt (Cook et al, 2011). Fig.…”
Section: Elimination Of Repeats In Mammals Affects the Extent Of Powementioning
confidence: 95%
“…It has been shown that inverted Alus, even at 86% identity, efficiently stimulate recombination when separated by b20 nt, while recombination still occurs at 80% identity (Lobachev et al, 2000;Stenger et al, 2001). In a recent work evidence is presented about deletions of Alu repeat pairs in inverse orientation separated by long distances, up to 350,000 nt (Cook et al, 2011). Fig.…”
Section: Elimination Of Repeats In Mammals Affects the Extent Of Powementioning
confidence: 95%
“…These repeats can also be interspersed throughout the genome, and can be arranged in direct or inverted orientations. However, inverted repeats are extremely unstable because they can form secondary structures that disrupt DNA replication, and consequently, are rarely seen (Cook et al, 2011; Kurahashi et al, 2009; Paek et al, 2009; Lobachev et al, 2002). Many tandem and interspersed repeats are active transposons such as Ty elements in yeast, or have their origins in transposable elements, the most common of which are Alu and LINE elements in humans.…”
Section: Types Of Repetitive Dna and Why They Existmentioning
confidence: 99%
“…Recombinant inverted Alu pairs have been shown to be unstable in genetically engineered yeast experiments when separated by up to 100 base pair (bp) and are potential sources of chromosome instability when separated by up to 350,000 bp in humans [18][20]. Furthermore, fusions of inverted Alu pairs previously separated by 1–5 kb have been recently identified at the breakpoints of high copy number loci in cancer cells [13].…”
Section: Introductionmentioning
confidence: 99%